Safety of urgent hip fracture surgery protocol under influence of direct oral anticoagulation medications. Issue 2 (February 2019) - Schermann, Haggai; Gurel, Ron; Gold, Aviram; Maman, Eran; Dolkart, Oleg; Steinberg, Ely L.; Chechik, Ofir
Highlights: No consensus exists regarding perioperative bleeding risks among patients treated with direct oral anticoagulants (DOACs). This is a retrospective cohort of hip fracture patients evaluating the effect of DOAC use on perioperative blood loss. DOAC use is not associated higher hemoglobin change perioperatively compared to no anticoagulation. DOAC use is not associated higher mortality one year after surgery compared to no anticoagulation. Abstract: Introduction: Direct oral anticoagulation agents (DOACs) are increasingly prescribed to older adults. Concerns for perioperative blood loss dictate cessation of anticoagulation treatment and postponement of surgery until the coagulation system returns to normal state. The goal of this study is to compare the estimates of perioperative blood loss and mortality between patients using DOACs and patients receiving no anticoagultaion, in order to challenge the existing policy and question the need for surgery deferral. Materials and methods: This is a retrospective cohort of patients (age > 65) with proximal hip fractures treated with either closed reduction internal fixation (CRIF, n = 1143; DOAC use n = 60) or hemiarthroplasty (HA, n = 571; DOAC use n = 29). Baseline patient characteristics included age, gender, ASA score, socioeconomic level, type of surgica#1: In general a l treatment, duration of surgery and time from admission to surgery. The effect of anticoagulant prescription on percentage of hemoglobin change, odds of receiving blood transfusions and one-month and one-year mortality was evaluated separately for CRIF and HA patients. Results: Patients receiving DOACs had similar perioperative hemoglobin change, transfusion rates and mortality, compared to subjects without anticoagulants in both CRIF and HA cohorts. DOAC patients undergoing CRIF had a longer delay to surgery (40.2 ± 26.9 vs 31.2 ± 22.2, p = 0.003) and higher mortality rates at one year postoperatively (26.7% vs 16.1%, p = 0.015). Conclusions: DOAC use was not associated with an increased perioperative blood loss or mortality compared to controls. However, they had to wait longer for surgery, which itself was an independent predictor of mortality. It may be safe to shorten waiting time for surgery in patients using anticoagulation, with the goal to minimize surgery delay.